Identification of Crystallized Ice on Kuiper Belt Objects - Hartwick, Victoria (Proceedings of the Wisconsin Space Conference, 2011)
The processes responsible for the presence and preservation of crystallized ice on Kuiper Belt Objects are presently unknown. However, a correlation between KBO radial size and its presence is potentially illuminative of dynamical and inter-object interactions throughout the history of the solar system. By analysis of three filter NIR observations of four Kuiper Belt Objects in combination with later observations, we hope to construct rough NIR spectra that indicate the presence or non-presence of crystallized ice on an object and together with other spectra confirm any existing correlations. My objective for the summer is to proceed with data reduction and analysis of my October observations of four Kuiper Belt Objects. Together with new observations in July, I can then construct up to 12 rough spectra and identify the presence of crystallized ice on objects of varying radii. A correlation between radial size and presence of crystallized ice will provide important information about the feasibility of current theorized processes for its creation and preservation.Â